Penanaman Nilai-Nilai Keagamaan Melalui Sholat Sempurna di TPQ An-Nur Bekiring - Ria Puspita Ayuningtyas; Hanafi Hadi Susanto (Social Science Academic, 2023)
The values of worship as a form of fostering Islamic religious education in Madrasahs are an effort to create quality human resources, so that they are able to compete in the era of globalization as is happening today while still upholding the teachings of Islam. For this reason, the teacher as the main actor in instilling religious and religious values to students requires certain strategies so that the values of worship can be absorbed and become part of the daily lives of students.So this study aims to determine the religious values that are instilled in the students of tpq an-nur bekiring through perfect prayer. Perfect prayer is prayer that is performed in accordance with the correct procedure, the correct movement, and the correctreading according to Islamic guidance. the difference with ordinary prayers is that ordinary prayers are performed only with movements as in general prayers, without knowing how to do the correct movements and how to recite the correct prayers, so it is an ordinary prayer. how to teach TPQ An-nur children, especially on the practice of Asr prayer by focusing on reading and prayer movements.The menthod used in this research is ABCD (Asset Based Comunity development), where the primary data is taken thruogh the observatoin menthod by going directly to the object of research in order to get the results in accordance with what the researcher expects.